Cultural connections - Mdleleni, Sinethemba (Rhodes University, 2026)
Many learners seem to struggle to grasp the concept of Newton’s laws in science, possibly due to decontextualised teaching methods used. To ameliorate this, the Curriculum Assessment and Policy Statement (CAPS) document recommends different teaching approaches, including the integration of Indigenous Knowledge (IK). However, it fails to mention how to integrate IK into the lessons. It is against this backdrop that this study sought to investigate how the use of the Indigenous mountain sliding game (umtyibilizi) can support the Grade 11 learners’ talk and sense making of the topic of Newton’s second law of motion. It is a qualitative case study that employed a participatory approach. It is underpinned by the interpretivist and Indigenous research paradigms. Ten Grade 11 Physical Sciences learners from Mqanduli in the Eastern Cape Province and two Indigenous Knowledge Custodians were participants in this study. In addition, a Physical Sciences teacher was a critical friend, who offered insights and feedback throughout the research process. Data generation methods involved focus group interviews (sharing circles), group activities, observations (participatory and lesson observations), and learners’ reflective journals. A thematic approach to data analysis was employed and concepts from Vygotsky’s sociocultural theory were used. The findings revealed that culturally relevant pedagogies, such as using umtyibilizi, facilitate learner engagement, collaborative learning and conceptual understanding. Umtybilizi ignited the interest amongst my learners to learn science. However, uneven participation and difficulties with scientific language continue to prevail. These findings support the promise of IK in facilitating and bridging the gap between cultural and scientific knowledge while also pointing to the continued need for targeted mediation in persisting learning difficulties.
teaching Newton’s second law through an Indigenous mountain sliding game (Umtyibilizi)
Keywords: Uncatalogued